PRINSIP COMPETITIVE NEUTRALITY DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA: The Principle of Competitive Neutrality in the Perspective of Competition Law - Muhammad Riziq Babeheer; Maria Tri Anggraini, Anna (Faculty of Law, Universitas Trisakti, 2026)
This study examines the principle of competitive neutrality from the perspective of competition law. This principle has become increasingly relevant as economic activities grow more complex and potentially create unequal treatment among business actors. The research problem focuses on how the principle of competitive neutrality is interpreted within Indonesian competition law, particularly under Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. This study employs a normative legal research method with a statutory and conceptual approach. The analysis is conducted on the provisions of Law Number 5 of 1999, supported by relevant literature and legal documents related to the principle of competitive neutrality. The results and conclusions show that the principle of competitive neutrality is not explicitly regulated under Law Number 5 of 1999. Nevertheless, its values and substance are consistent with the objectives of competition law in promoting fair competition and preventing unjust advantages for certain business actors. Therefore, the principle of competitive neutrality can serve as a conceptual basis to interpret and strengthen the enforcement of competition law in Indonesia in order to maintain a level playing field.